Fractal characteristics of methane migration channels in inclined coal seams. (15th June 2021) - Zhao, Pengxiang; Zhuo, Risheng; Li, Shugang; Shu, Chi-Min; Jia, Yongyong; Lin, Haifei; Chang, Zechen; Ho, Chun-Hsing; Laiwang, Bin; Xiao, Peng
Abstract: Methane safety extraction is an effective method for reducing methane concentration in the gob and enhanced coal-bed methane recovery that is widely used in China. Although there is already extensive research on this technique, dip angle coal of seams has unpredictable effects on methane extraction locations, which is an influential factor that has rarely been studied, especially where the seam dip angles are larger. The benefits of this paper include improving methane extraction techniques, exploring the fractal characteristic of channel, and developing the laws governing how channels emerge, especially where coal seam dip angles vary. The results show that with increased coal seam dip angle, the height and width of channels show an increasing trend, along with crack angle. Key parameters of the methane migration channel boundaries in mutant regions of the bed separated under inclined coal mines were also defined. In the laboratory, an effective model was put forward to calculate the evolution characteristics of channels under inclined coal mining using fractal and elliptic paraboloid zone theory (EPZ); the finding was that the height of the A region at 30° was 1.34 and 2.00 times that of 15°, 0°, respectively. Moreover, borehole methane extraction concentration in area B increased to 6.04% in field application. The research results are expected to benefit industry and mine safety staff when arranging the position of high-level boreholes. The findings can enhance safety levels and improve efficiency in inclined coal mining. Highlights: A model for fractal dimension under inclined coal mine prediction proposed. The main controlling factors for the methane migration channel was identified. It was divided into three areas by fractal dimension in vertical gradient. The model can estimate high-level borehole position under inclined coal mine.